Constructs across a hierarchical, dimensional model of psychopathology show differential associations with social and general cognitive ability. - Scott D Blain; Jerillyn S Kent; Timothy A Allen; Carly A Lasagna; Chloe A Peyromaure de Bord; Aisha L Udochi; Scott R Sponheim; Colin G DeYoung; Ivy F Tso (PLoS ONE)
Many psychiatric disorders and associated psychopathology dimensions are related to social cognitive deficits and reduced general cognitive ability. The current study applied a hierarchical, dimensional approach to better understand associations among psychopathology, social cognition, and general cognitive ability. Data were collected from two samples (n = 653), including psychosis-spectrum patients, their first-degree relatives, and individuals from community sources. Participants completed dimensional psychopathology measures and social cognition tasks (e.g., emotion perception and mentalizing). Data were analyzed using bi-factor exploratory structural equation modeling. Detachment-a psychopathology dimension conceptually linked to social functioning-was associated with worse social cognition, independent of general cognitive ability. Eccentricity and Machiavellianism were associated with better social cognition and general cognitive ability. Findings-and the hierarchical, dimensional approach employed-will be useful in informing future research on and interventions for social dysfunction.